Applications of management science. - Lawrence, Kenneth D.; Kleinman, Gary (Applications of management science ;, 2018)
Applications of Management Science is a blind refereed series that is published on an annual basis. Its objective is to present current studies in the application of management science to the solution of significant managerial decision-making problems. It significantly aids in the dissemination of the solution of managerial decision-making problems with management science methodologies. Volume 19 focuses on the application of management science methodologies, data envelopment analysis and multi-criteria decision making. The first section is focused on data envelopment analysis. The second section focuses on multi-criteria decision making. The third section focuses on decision making.This volume will be of significant interested to those involved in the applications of multi-criteria decision making, data envelopment analysis and decision making, in a realistic managerial problem solving environment through the use of state-of-the-art management science modelling.